(untitled) (Scientific journal of the Fergana State University, 2024)
This article talks about the importance of healthy walking according to the Nordic method in preserving and strengthening the health of the population, its positive effect on the human body, legal rules for conducting exercises, as well as the difference between Nordic walking and other sports.